Inequality and risk preference - Harry Pickard; Thomas Dohmen; Bert Van Landeghem (Journal of Risk and Uncertainty, 2024)
This paper studies the relationship between income inequality and risk taking. Increased income inequality is likely to enlarge the scope for upward comparisons and, in the presence of reference-dependent preferences, to increase willingness to take risks. Using a globally representative data set on risk preference in 76 countries, we empirically document that the distribution of income in a country has a positive and significant link with the preference for risk. This relationship is remarkably precise and holds across countries and individuals, as well as alternate measures of inequality. We find evidence of a steeper gradient between willingness to take risks and inequality for cognitively more able individuals who likely have a better assessment of inequality and for those who are dissatisfied with their income. We present results in favour of our mechanism, which suggests that falling behind one's reference group increases the appetite for risk taking.
Keywords: D91; O15; D81; D01; 300; Income inequality; Risk preference; Risk sensitivity